Thermally Stable Super Ionic Conductor from Carbon Sphere Oxide. Issue 16 (26th July 2016) - Islam, Md. Saidul; Karim, Mohammad Razaul; Hatakeyama, Kazuto; Takehira, Hiroshi; Ohtani, Ryo; Nakamura, Masaaki; Koinuma, Michio; Hayami, Shinya
Abstract: A highly stable proton conductor has been developed from carbon sphere oxide (CSO). Carbon sphere (CS) generated from sucrose was oxidized successfully to CSO using Hummers' graphite oxidation technique. At room temperature and 90 % relative humidity, the proton conductivity of thin layer CSO on microsized comb electrode was found to be 8.7×10 −3  S cm −1, which is higher than that for a similar graphene oxide (GO) sample (3.4×10 −3  S cm −1 ). The activation energy ( E a ) of 0.258 eV suggests that the proton is conducted through the Grotthuss mechanism. The carboxyl functional groups on the CSO surface are primarily responsible for transporting protons. In contrast to conventional carbon‐based proton conductors, in which the functional groups decompose around 80 °C, CSO has a stable morphology and functional groups with reproducible proton conductivity up to 400 °C. Even once annealed at different temperatures at high relative humidity, the proton conductivity of CSO remains almost unchanged, whereas significant change is seen with a similar GO sample. After annealing at 100 and 200 °C, the respective proton conductivity of CSO was almost the same, and was about ∼50 % of the proton conductivity at room temperature. Carbon‐based solid electrolyte with such high thermal stability and reproducible proton conductivity is desired for practical applications. We expect that a CSO‐based proton conductor would be applicable for fuel cells and sensing devices operating under high temperatures. Abstract : Good conduct : Carbon sphere oxide (CSO) obtained from oxidation of sucrose carbon spheres exhibits higher proton conductivity (8.7×10 −3  S cm −1 ) than that for a similar graphene oxide sample (3.4×10 −3  S cm −1 ). The conductivity is sustained even after CSO is annealed at 400 °C.